THE RESEARCH ON THE NECESSITY OF CORPORATE IDENTITY DEVELOPMENT FOR THE EASTERN LATVIAN HIGH SCHOOL OF TECHNOLOGIES - Poseva, Diana; Strode, Aina (ARTS AND MUSIC IN CULTURAL DISCOURSE. Proceedings of the International Scientific and Practical Conference, 2016)
Every person, group or organization has its own identity, which helps to define the most important values, events and stand out among competitors. Eastern Latvian High School of Technologies is a newly established school, which opened its doors in September 2015. Therefore the corporate identity is the key issue in the popularization of this school. The objective of this research is to find out the necessity of the corporate identity development for the Eastern Latvian High School of Technologies by studying and analyzing the importance of branding in the area of education. The methods of research: theoretical – investigation and analysis of relevant literature, internet sources and regulatory documents. Empirical – methods of data collecting: survey, structured interview.